One dimensional ZnWO4 nanorods coupled with WO3 nanoplates heterojunction composite for efficient photocatalytic and photoelectrochemical activity. Issue 3 (1st February 2022) - Kumar, G. Mohan; Lee, D.J.; Jeon, H.C.; Ilanchezhiyan, P.; Deuk Young, Kim; Tae Won, Kang
Abstract: In this study, we report a novel semiconductor heterojunction of ZnWO4 /WO3 composite successfully constructed through one-pot facile and eco-friendly in situ hydrothermal synthesis. The structural, morphological and photophysical property of ZnWO4 /WO3 composite were investigated by powder X-ray diffraction (XRD), Raman spectrum, scanning electron microscope (SEM), high resolution transmission electron microscope (HRTEM), photoluminescence (PL) and transient photocurrent response. The morphological analysis indicated that ZnWO4 nanorods are well distributed on the surface of WO3 nanoplates. The ZnWO4 /WO3 heterojunction composite possess strong light absorption in the visible region. To explore the photocatalytic activity of the prepared ZnWO4 /WO3 heterojunction composite methylene blue (MB) was chosen as organic dye to assess the degradation ability of composite under visible light treatment. ZnWO4 /WO3 heterojunction composite showed remarkable photocatalytic activity than that of pristine ZnWO4 and WO3 . The elevated photocatalytic activity is attributed to the formation of heterojunction interface between WO3 and ZnWO4, leading to effective transfer and separation of photogenerated carriers in heterojunction. A plausible mechanism for the superior photocatalytic degradation over ZnWO4 /WO3 heterojunction composites was also proposed.